2006
DOI: 10.1002/jsc.746
|View full text |Cite
|
Sign up to set email alerts
|

Net present value: the illusion of certainty

Abstract: ᭹Too many fashionable strategic change 'solutions' suppose that uncertainty can be eliminated. This paper considers one such technique -net present value -and rejects its claimed ability to effectively determine the profitability of major future investment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…According to Nichols, Slender, and Luehrman (1994), the intent of the Research Planning Model as used by Merck & Company, Incorporated, is to use probability distributions to produce a range of various results that will be used to forward discussion and decision-making. McGrath (1997) (McSweeney, 2006). Capital Budgeting tools employ discrete mathematical techniques that assume a linear and predictable relationship exists between managerial decisions and the performance of a venture.…”
Section: Sources Of Real Options Emanate From Existing Investments (Smentioning
confidence: 99%
“…According to Nichols, Slender, and Luehrman (1994), the intent of the Research Planning Model as used by Merck & Company, Incorporated, is to use probability distributions to produce a range of various results that will be used to forward discussion and decision-making. McGrath (1997) (McSweeney, 2006). Capital Budgeting tools employ discrete mathematical techniques that assume a linear and predictable relationship exists between managerial decisions and the performance of a venture.…”
Section: Sources Of Real Options Emanate From Existing Investments (Smentioning
confidence: 99%
“…Hence, the method provides values under the assumption of a static and certain world (McSweeney 2006). McCloskey (1991) raises caveat over the seeming sureness and precision of economic models.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…It is suggested that the real problem McSweeney (2006) highlights lies with the approach of management to forecasting this range of variables and the critical objectivity which the forecasting capability of the organization systems permits. Even if the final stage of the NPV calculation was dispensed with, the basic causes of forecasting inaccuracy and lack of managerial judgement would still be present.…”
Section: Forecasting and Evaluationmentioning
confidence: 99%
“…McSweeney (2006) reminds us of Napoleon's tempestuous visit to Russia in 1812. There was another visitor to that country somewhat earlier, whose experience was also most illuminating.…”
Section: Introductionmentioning
confidence: 99%